INOVASI PENGOLAHAN SAMPAH DI DESA NGESTIHARJO UNTUK MENDUKUNG GERAKAN BANTUL BERSAMA - Sari, Marti Widya; Setyo Nugroho, Ginanjar; Syah, Firdiyan (Universitas PGRI Yogyakarta, 2023)
Padukuhan Tambak, Ngestiharjo Urban Village, Bantul, has a high population density and has a waste problem which is the main issue. Narrow land makes it more difficult for residents to dispose of garbage around their homes, besides that residents throw garbage carelessly, even in river basins, which causes the river to overflow during the rainy season and causes an unpleasant smell. The urgency of this PKM activity is the need to unravel and overcome waste problems to support the Bantul Bersama program, by empowering the community from the lowest level (village level). Partners in this activity are the Mitra Melati Garbage Bank Group (KBS) in Padukuhan Tambak. Priority problems faced by partners are 1) they do not understand waste management, 2) waste segregation is not optimal, 3) lack of skills in managing waste savings/alms, and 4) waste residues are not managed properly. The purpose of this PKM activity is to unravel the problems of waste management in Padukuhan Tambak, to assist partners in dealing with waste management to support the realization of the 2025 Bantul Bersama program. Keywords: Waste management, Bantul Bersama, Empowerment, Garbage Bank